1960
DOI: 10.1161/01.res.8.4.871
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Genuine Autoregulation of the Renal Circulation

Abstract: The mechanism causing renal vascular flow to vary less than proportional to changes in arterial-venous pressure gradient, was studied in isolated dog kidneys perfused with whole blood and with cell-free colloidal solutions. This autoregulation of renal flow rapidly deteriorated along with vascular reactivity to drugs when oxygenated polyvinyl-pyrrolidone-Locke solution was used for perfusion. This deterioration was prevented by the addition of plasma to the colloidal perfusate. During the first 2 sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
3

Year Published

1964
1964
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 31 publications
2
28
0
3
Order By: Relevance
“…The phenomenon of autoregulation has been reported for several vascular beds including kidney, 2 intestine, 3 ' 4 brain, 5 and heart. 0 A number of investigators '• 7 " n have confirmed the early observations of Bayliss 12 who reported autoregulation in skeletal muscle.…”
mentioning
confidence: 96%
“…The phenomenon of autoregulation has been reported for several vascular beds including kidney, 2 intestine, 3 ' 4 brain, 5 and heart. 0 A number of investigators '• 7 " n have confirmed the early observations of Bayliss 12 who reported autoregulation in skeletal muscle.…”
mentioning
confidence: 96%
“…It is more likely that the reductions in RBF in all three groups were due to hypotension beyond the normal range of renal autoregulation, because RBF intrinsically autoregulates with change in MAP from 80 to 180 mmHg in dogs. 22 In addition, SNP has only a weak vasodilating activity on the renal vasculature. 23,24 Because hypotension within the autoregulatory pressure range of the renal vasculature has been shown to result in redistribution of blood flow from the outer cortical layers to juxtamedullary layers, 25 mechanisms responsible for RBF reductions may cause a maldistribution of RBF within the autoregulation process.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
“…Autoregulation was tested during both aqueous and oil perfusions by rapidly induced changes in renal arterial pressure, with observance of whether square wave changes in pressure were associated with square wave changes in organ outflow [30] or with rapid phasic adjustments in flow rate [30]. Steady state flow rates were meas ured directly shortly before arterial pressure elevation, after 1.5-2 min of raised arterial pressure, and again 1-2 min after reduction of arterial pressure to a level near the initial 'control' perfusion pressure.…”
Section: Dog Kidney Experimentsmentioning
confidence: 99%
“…In 4 of 9 dog kidneys, reuse of once-perfused colloidal solution was required before autoregulation was well manifested, because of the finding of little or not autoregulation during the first 10-20 min of isolated perfusion with synthetic colloidal solution, as previously found when the colloidal perfusate was devoid of plasma [30], and because of depletion of the initial reser voir supply of colloidal perfusate.…”
Section: Dog Kidney Experimentsmentioning
confidence: 99%
See 1 more Smart Citation